WPŁYW NOWELIZACJI KODEKSU POSTĘPOWANIA KARNEGO NA ZAKRES KARNOPROCESOWYCH UPRAWNIEŃ ŻANDARMERII WOJSKOWEJ - Jastrzębski, Wińczysław (Zeszyty Prawnicze, 2016)
On 1st July 2015 Art. 321 of the recently amended code of Polish criminal procedure (kodeks postępowania karnego, k.p.k.) enlarged the scope of powers of the Polish Military Police (Żandarmeria Wojskowa, ŻW) in criminal proceedings. In this respect ŻW now has the powers defined in the Military Police Act (ŻWU), while the respective powers of military prosecutors and courts have remained unchanged. Since 1st July 2015 ŻW has held the appropriate powers both with respect to soldiers regardless of the circumstances in which they committed an offence, and with respect to civilians violating the law in a military zone. The powers of the Polish Military Police have not been changed in cases of minor and tax offences, and correspond to the jurisdictive powers exercised by military courts. In this article the author analyses the scope of the changes in the powers held by the Polish Military Police regarding procedure in criminal cases, and on the basis of a comparison of the changes with ŻW’s structure and duties assesses the effects of the amendment, concluding that their impact goes well beyond the military community.